Interactions between plant growth and soil moisture determine the N2O source strength of farmed landscape depressions - Yujia Liu; Björn Kemmann; Per Ambus; Bo Elberling; Michael Dannenmann; Kristian Thorup-Kristensen; Daniel M. N. Poultney; Carsten W. Mueller (Plant and Soil, 2026)
Background Topographic depressions within agricultural fields contribute disproportionately to regional nitrous oxide (N 2 O) emissions. These low-lying areas accumulate nutrients and fine particles through water inflow and erosion, creating conditions conducive to elevated N 2 O emissions. Because depressions remain part of fields, understanding how crop presence and management influence their N 2 O source strength is essential. Methods A greenhouse mesocosm experiment was conducted using soil collected from an agricultural depression under either drained or partially waterlogged conditions (water table maintained 10 cm below the soil surface). Wheat was sown at three dates (57, 43, and 29 days before waterlogging) to represent different vegetative stages and capacities for N uptake. Dissolved organic carbon (DOC), dissolved nitrogen (N), root growth, and N 2 O emissions were continuously monitored. A 15 N-labelled fertilizer was applied during the waterlogging period to trace fertilizer-derived N in emitted N 2 O, soil, and plant biomass. Results Early-sown wheat was more strongly impaired by waterlogging than later-sown treatments but nevertheless significantly reduced N 2 O emissions compared with the unplanted control, irrespective of water regime. Early-sown plants also acted as stronger N sink, indicating that greater plant N acquisition contributed to reduced N availability for N 2 O production. In contrast, trends in DOC and cumulative N 2 O emissions across seeding dates were less consistent, particularly under waterlogged conditions. Conclusions Plant N uptake emerged as the primary mechanism reducing N 2 O emissions under the tested conditions. Although a general trend of lower N 2 O emissions with increasing plant age and N uptake was observed, the relationship was not strictly linear, due to plant age-specific interactions with waterlogging. Nevertheless, the results suggest that establishing crops in depression areas can mitigate N 2 O emissions by strengthening plant competition for available N, while the magnitude of this mitigation depends on both seeding date and waterlogging conditions.

Effect of short-term warming on total and potentially active prokaryotic communities in Arctic soil - Gabriele Tosadori; Frances Rose Gilman; Daan Blok; Carsten Suhr Jacobsen; William Holben; Anders Michelsen; Bo Elberling; Anders Priemé; Jana Voříšková (Applied Soil Ecology, 2026)